2015
DOI: 10.1148/radiol.2015141638
|View full text |Cite
|
Sign up to set email alerts
|

Early Metabolic Response to Neoadjuvant Treatment: FDG PET/CT Criteria according to Breast Cancer Subtype

Abstract: Quantitative indexes of tumor glucose use that are best correlated with pathologic response vary by phenotype: change in SUV(max) or TLG are most adequate for TNBCs and ER-positive/ HER2-negative cancers and absolute SUV(max) after two cycles of chemotherapy for HER2-positive breast cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 40 publications
4
68
0
3
Order By: Relevance
“…There was no significant difference in uptake between NG1 and NG2. (19). Triple-negative breast tumors demonstrated the highest mean uptake, followed by ER1/HER22 and lowest uptake in HER21 type though without overall significance likely due to small sample size (Table 3).…”
Section: F-fluciclovine Activity and Histologic Characteristics Of Brmentioning
confidence: 94%
“…There was no significant difference in uptake between NG1 and NG2. (19). Triple-negative breast tumors demonstrated the highest mean uptake, followed by ER1/HER22 and lowest uptake in HER21 type though without overall significance likely due to small sample size (Table 3).…”
Section: F-fluciclovine Activity and Histologic Characteristics Of Brmentioning
confidence: 94%
“…The imaging protocol was designed to ensure SUV measurements across all time points. Blood glucose levels were measured in all patients before 18 F-FDG administration; no patient had blood glucose levels exceeding 200 mg/dL. After fasting for at least 6 h, the patients received an intravenous injection of 18 F-FDG (3.7-4.0 MBq/kg).…”
Section: F-fdg Pet/ct Scan Proceduresmentioning
confidence: 99%
“…Presently, 18 F-FDG PET combined with CT is accepted as a noninvasive method for the early evaluation of the response to therapy because decreased glucose metabolism precedes tumor shrinkage (2). However, the expensive technology using 18 F-FDG PET/CT during NAC has precluded its integration into clinical practice (3). Near-infrared optical imaging based on the visualization of the hemodynamic status of the tissue (such as oxyhemoglobin [O 2 Hb] and deoxyhemoglobin [HHb] concentrations) is reportedly promising for determining the physiologic status of tumor-bearing breast tissue and for monitoring early responses (4).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies found that early changes in tumor glucose metabolism, assessed with 18 F-FDG PET/CT after the first or second course of neoadjuvant chemotherapy, can indicate breast cancer response early (5,6), especially in the aggressive TNBC subtype (7,8).…”
mentioning
confidence: 99%